REQUIREMENTS FOR MODERN MANAGEMENT PERSONNEL (Conference Zone, 2021)
A leadership style is a way of making decisions and delegating tasks to executors. The best style is the one that gives the best results. The leadership style, therefore, provides feedback on how the leader can motivate the team to perform the tasks assigned to him, and how he can control the performance of his subordinates.